2019
DOI: 10.1371/journal.pone.0216115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic dispensing practice in community pharmacies in Jordan: A cross sectional study

Abstract: It is well known that the emergence of antibiotic resistance is linked to the misuse and overuse of antibiotics. Misuse includes self-medication and the inappropriate use of antibiotics because of improper dosage or improper duration than recommended. This study investigated three patterns of dispensing antibiotics in a sample of community pharmacies in Jordan. This included dispensing antibiotics by prescription or over-the-counter either by direct request or upon a pharmacist’s recommendation. The antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 21 publications
5
71
0
Order By: Relevance
“…A four-month observational study in Jordan found that less than 70% of antibiotics dispensed were physician prescribed, and only 31.5% of those drugs were prescribed at the correct dosage and for the correct duration. Lower socioeconomic status and poor education were driving factors for self-medication, which was consistent with similar studies [72,73]. A cross-sectional, client simulation study in Surabaya, Indonesia, investigated common dispensation practices in the country.…”
Section: Antibiotic Stewardshipsupporting
confidence: 81%
“…A four-month observational study in Jordan found that less than 70% of antibiotics dispensed were physician prescribed, and only 31.5% of those drugs were prescribed at the correct dosage and for the correct duration. Lower socioeconomic status and poor education were driving factors for self-medication, which was consistent with similar studies [72,73]. A cross-sectional, client simulation study in Surabaya, Indonesia, investigated common dispensation practices in the country.…”
Section: Antibiotic Stewardshipsupporting
confidence: 81%
“…Almaayta and colleagues [ 42 ] reported that of 202 pharmacies visited, 150 dispensed antibiotics without a prescription, mainly for the treatment of sore throat, urinary symptoms, and diarrhea. Another study reported that one third of antibiotics dispensed at local pharmacies were unprescribed [ 43 ]. A cross-sectional study from Irbid done by Yusef and colleagues reported that almost 40% of the participants who received antibiotics did not have a prescription [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe and North America, outpatient antibiotic dispensing (OAD) is often prescription-only [ 3 ] but can be accessed without prescriptions in many countries of the global South [ 4 , 5 ]. In 1988, Syria’s Ministry of Health legislated to determine which drugs could be sold over-the-counter.…”
Section: Introductionmentioning
confidence: 99%